Критерії та рівні духовно-морального розвитку особистості у процесі роботи православних недільних шкіл на Волині - Гелета, Олена; Heleta, Elena (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті визначено критерії та рівні духовно-морального розвитку особистості у процесі роботи православних недільних шкіл на Волині. Розкрито сутність, мету, завдання та особливості духовного розвитку особистості. З’ясовано, що найважливішим елементом у сучасній системі духовно-морального виховання є впровадження духовних цінностей на ґрунті православної культури. У статті обґрунтовується актуальність та необхідність духовно-морального виховання підростаючого покоління на християнських цінностях. Розкриваються перспективи духовно-морального виховання дітей у недільних школах. The article deals with the essence and peculiar properties of personality formation in the concept of Christian spiritual and moral values. It states the purpose, task and peculiar features of a child’s spiritual world formation.Urgency and necessity of spiritual and moral education of the younger generationto Christian values.In the article the analysis of component lexical construction of spiritual-moral education of pupils in general schools is conducted, concordance of lexemes "spiritual", "spirituality", "moral", "morality" is done.Uncover the prospect of spiritual and moral education of Orthodox Sunday schools in Volyn region. Moral education is a purposeful process that combines different means of religious and moral control over a child’s education which is aimed at training and educating a spiritual person with a good knowledge of their rights, obligations, and responsibility for their actions. Nowadays religious and moral education is very important as it is inclined:to educate a person that seeks self-perfection and the likeness of God;to educate a person who knows that their soul will be responsible before God for all their good and bad deeds; educate the person that is willing to follow Christian norms of behavior.
Criteria’s and degrees of spiritual and moral means in process of Orthodox Sunday schools in Volyn region
Keywords: духовність; духовно-моральне виховання; духовна культура; spirituality; spiritual and moral education; spiritual culturе